2022
DOI: 10.1002/pros.24311
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and meta‐analysis of placebo effect in clinical trials on chronic prostatitis/chronic pelvic pain syndrome

Abstract: Background It is a common practice to control efficacy of pharmacological treatment with a placebo group. However, placebo itself may affect subjective and even objective results. The purpose of this study was to evaluate the placebo effect on symptoms of CP/CPPS to improve future clinical trials. Methods A search at three databases (Scopus, MEDLINE, and Web of Science) was conducted to identify double‐blind placebo‐controlled clinical trials on the treatment of CP/CPPS published until April 2021. The primary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 61 publications
(142 reference statements)
0
3
0
Order By: Relevance
“…Placebo and nocebo effects on pain have been extensively studied using experimental research designs [ 6 , 11 , 12 , 13 , 14 , 15 ]. Different approaches have been used to trigger pain amelioration or exacerbation: the two most common procedures are (1) the use of positive or negative expectations and (2) the use of conditioning approaches [ 11 , 12 ].…”
Section: State Of the Artmentioning
confidence: 99%
“…Placebo and nocebo effects on pain have been extensively studied using experimental research designs [ 6 , 11 , 12 , 13 , 14 , 15 ]. Different approaches have been used to trigger pain amelioration or exacerbation: the two most common procedures are (1) the use of positive or negative expectations and (2) the use of conditioning approaches [ 11 , 12 ].…”
Section: State Of the Artmentioning
confidence: 99%
“…CP/CPPS is often misdiagnosed as prostatitis and is commonly treated with antibiotics. However, in recent years, some studies have shown that pharmacological treatments do not have a significant effect and maybe even no difference from placebo [ 33 , 34 ]. The pathogenesis of CP/CPPS is currently unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Then 299 articles were excluded after reviewing the titles and abstracts, leaving 107 records for fulltext screening. Finally, 62 records were further excluded and 45 SRs/MAs were included in our study [6,7,.…”
Section: Literature Searchmentioning
confidence: 99%
“…Based on the classification system of prostatitis syndromes established by the National Institute of Health (NIH) in 1999, CP/CPPS can be divided into two subtypes: IIIA (inflammatory), and IIIB (Noninflammatory), accounting for about 90-95% of all prostatitis cases [4]. The manifestations of CP/CPPS were heterogeneous, mainly including urogenital pain, lower urinary tract symptoms (LUTS), psychological problems, and sexual dysfunction [5,6]. The disorder not only impairs the quality of life (QOL) of patients but often leads to severe psychosocial and economic burdens [3,6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation